The predisposition of Small and Medium Scale Enterprises (SMEs) to penetrate international market: a focus on Agro based sector / Nur Hafizah Jaafar - Jaafar, Nur Hafizah (2009)
The study was done between December 2008 and April 2009 to identify the predisposition of SME in penetrating international market by focusing in the manufacturing agro based sector. Fifty SMEs Company comprising in Selangor and Kuala Lumpur were selected using the method of random sampling. The problem statement here is to find the factors that affecting predisposition of Small Medium Enterprises (SMEs) in Malaysia to penetrate international market by focusing on the manufacturing (agro based) sectors. The Objectives are to identify the predisposition of SMEs in penetrating international market, to study the most influencing factors that influence SMEs in penetrating international market and the relationship between independent variable and dependent variable. A descriptive analysis of the data was done using the Statistical Package for the Social Sciences (SPSS) and correlation model was used to analyze the relationship between dependent variable and independent variable. The results showed that five variables are significant with the dependent variable. Some recommendations emanating for financial aid, government should provide business advice, training and finance to small business enterprises. For adoption of technology, government should encourage the development of websites. Then, for managerial competitiveness, government should introduce the programme in collaboration with Malaysia Institute of Management, for the programme as every organization needed the great managers. For MNCs competitiveness, government will provide support for example legal documentation to establish relationships with clients in international markets. Lastly for the conducive government policies, government should establish evaluation frameworks by sustaining, reconsidering and increasing levels of support.